Kajian Estetika dan Unsur Pendukungnya pada Keraton Surakarta - Imam Santosa (ITB Journal Publisher, LPPM ITB, 2007)
In Javanese culture, the Keraton of Surakarta Hadiningrat (Surakarta Hadiningrat Palace) is classified as one of the highly valued Javanese historical objects. It is due to the fact that the history of the Palace's construction has a close connection with the history of the previous Javanese kingdoms, especially those belong to the Mataram Rajakula (dynasty) which was established in the year 1508 of Javanese calendar (Saka) or 1582 AD. The word